Budaya Mutu Berbasis Industri (BUTUISTRI) Sebagai Upaya Peningkatan Mutu Lembaga Pendidikan Islam di Kawasan Industri Gresik - Hidayatul Mufidah (Wibawa : Jurnal Manajemen Pendidikan, 2024)
One of the Islamic educational institutions is located in the Gresik industrial area, so it has an influence in forming a quality culture. One of them is the industry-based quality culture that occurs at SMK Nurul Islam. This study aims to determine the form of industry-based quality culture in improving quality at SMK Nurul Islam, the implementation of industry-based quality culture in improving quality at SMK Nurul Islam, obstacles and solutions to industry-based quality culture in improving quality at SMK Nurul Islam. The study uses descriptive qualitative research. Using observation, interview and documentation data collection methods. While the data analysis techniques used are data collection, data reduction to drawing conclusions. The results of the study are the form of industry-based quality culture in improving quality at SMK Nurul Islam as follows, Students and educators and education staff at SMK Nurul Islam have created an environmental atmosphere as in the work environment such as students at 06.45 WIB must be present using Finger Print to register attendance at school, Students wear uniforms which are usually worn in the industrial world., Educators are included in internship activities in the industrial world, The curriculum has been Linked and Matched with the industrial world or business world, In learning there are industrial classes that are included in the curriculum and learning activities, In terms of improving the quality of facilities and infrastructure, SMK Nurul Islam has used the layout of facilities and infrastructure that has used several layouts that exist in the industrial world. With the implementation of industry-based quality culture in this school, it can be said that there are several quality improvements at SMK Nurul Islam. For the development of industry-based culture, SMK Nurul Islam often conducts comparative studies to several industrial worlds to innovate in forming an industry-based quality culture. The form of quality improvement with the existence of an industry-based quality culture at SMK Nurul Islam is in the quality of facilities and infrastructure, the quality of educators, the quality of students and even the quality of learning that has increased. Obstacles and Solutions to an industry-based quality culture in improving the quality of SMK Nurul Islam are Teachers and Foundation Management. The solution is to often introduce an industry-based quality culture to teachers so that they can implement it well. Communication with the foundation about the management of SMK Nurul Islam, introducing the foundation about the integration of an industry-based quality culture into school management